تقصي المتطفلات الحشرية Parasitoids المرافقة لحشرة الحمضيات الرمادية Parlatoria pergandii في بعض بساتين الحمضيات في محافظة اللاذقية - بشير عبد النبي; أبو كف نبيل; محمد اياد (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة خلال موسمي 2005-2006 وتم جمع العينات من بساتين حمضيات تابعة لقرى محافظة اللاذقية (البصة, واسطامو, وطرجانو, وحميميم) وهدفت هذه الدراسة إلى تحديد المتطفلات الحشرية المرافقة لحشرة الحمضيات القشرية الرمادية والارتباط بين هذه المتطفلات والطور المفضل من العائل الذي تهاجمه.تم تسجيل 6 أنواع من المتطفلات الحشرية المرافقة لحشرة الحمضيات الرمادية في مناطق الدراسة تتبع هذه المتطفلات لرتبة غشائيات الأجنحة Hymenoptera فوق فصيلة Calcidoidea فصيلة Aphelinidae أربعة من هذه المتطفلات هي متطفلات خارجية Exoparasitoids تتبع الجنس Aphytis و هي: A.melinus, (Debach) A.maculicornis (Masi) A.hispanicus, A.chrysomphali( Merect) واثنان منها هي متطفلات داخلية تتبع الجنس Encarsia ( Prospoltella) وهي E.citrina(Craw), E.enquirenda (Silvestri)، وكانت أعلى نسبة للتطفل في عام 2005هي 33.6 في شهر تشرين الأول وأدناها في شهر شباط 11.32 أما في عام 2006 فكانت 31.25 في شهر تشرين الأول وأدناها في شهر شباط 11.33، ومن المفيد ذكره أن المتطفلات A.maculicornis,, A.hispanicus, E.citrina, E.enquirenda تسجل لأول مرة في القطر مترافقة مع انتشار الحشرة القشرية الرمادية في بيئة زراعة الحمضيات في الساحل السوري. The study was conducted during 2005-2006. The samples were collected from citrus orchards in Lattakia governorate (Albassa –Stamo - Tergano- Hmemim). The aim of this study is to determine parasitoids associated with chaff scale parlatoria pergandii Comstock and environmental correlation between parasitoids and their preferable host stage. During this study, six parasitoids were found associated with chaff scale; these parasitoids followed Hymenoptera: Calcidoidea: Aphelinidae. Four parasitoids are ectoparasitoids: Aphytis hispanicus( Merect), A.chrysomphali A.melinus (Debach), A.maculicornis (Masi). Two parasitoids are endoparasitoids: Encarsia citrina(Craw), E.enquirenda (Silvestri). The high average of parasitism was in October (33.6), and the low average was in February (11.32) in 2005, but in 2006 the high average of parasitism was in October (31.25) and the low average was in February (11.33). It worth mentioning here that these parasitoids- A.maculicornis, A.hispanicus, E.citrina, E.enquirenda- are recorded for the first time in Syria associated with Parlatoria pergandii on citrus.